2020
DOI: 10.1785/0220200181
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of the Interfrequency Correlation of Synthetic Ground Motions to Pseudodynamic Source Models

Abstract: Given the deficiency of recorded strong ground-motion data, it is important to understand the effects of earthquake rupture processes on near-source ground-motion characteristics and to develop physics-based ground-motion simulation methods for advanced seismic hazard assessments. Recently, the interfrequency correlation of ground motions has become an important element of ground-motion predictions. We investigate the effect of pseudodynamic source models on the interfrequency correlation of ground motions by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…We focus on the evaluation component of validation because the parameters or techniques which drive the inter-frequency correlations are not well understood in simulations like CyberShake NZ v20.11. One promising pilot study investigated the effect of pseudo dynamic source models on inter-frequency correlations and found that cross-correlation between source parameters (slip, rupture velocity, and peak slip velocity) affects the inter-frequency correlation around 0.5 Hz [3]. Additional similar studies are needed to identify the causal features of the inter-frequency correlation in simulations, and these should identify techniques for future calibrations and validations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We focus on the evaluation component of validation because the parameters or techniques which drive the inter-frequency correlations are not well understood in simulations like CyberShake NZ v20.11. One promising pilot study investigated the effect of pseudo dynamic source models on inter-frequency correlations and found that cross-correlation between source parameters (slip, rupture velocity, and peak slip velocity) affects the inter-frequency correlation around 0.5 Hz [3]. Additional similar studies are needed to identify the causal features of the inter-frequency correlation in simulations, and these should identify techniques for future calibrations and validations.…”
Section: Discussionmentioning
confidence: 99%
“…As a step in the right direction, Song et al [3] investigated the effect of pseudo-dynamic source models on the inter-frequency correlation of ground-motions by simulating the 1994 Northridge, California, earthquake, using the SCEC BBP. The authors found that the cross correlation between earthquake source parameters (slip, rupture velocity, and peak slip velocity) in the pseudo-dynamic source models significantly affected the inter-frequency correlation of ground-motions in the frequency around 0.5 Hz, whereas this effect was not visible in the other frequency ranges.…”
Section: Calibration Of Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subsequent evaluations of 3D SCEC CyberShake (Los Angeles, California) and QuakeCore CyberShake (New Zealand) simulations by Bayless and Abrahamson showed substantial improvements in the inter-period FAS correlations at long periods relative to the one-dimensional (1D) BBP simulations (unpublished findings from SCEC and QuakeCore projects, obtained from personal communications with Bayless, 2022). Later, Song et al (2021) investigated the effects of pseudo-dynamic source models on the inter-period correlation of ground motions by simulating the 1994 Northridge, California, earthquake, using the BBP. They found that the cross-correlation between earthquake source parameters in the pseudo-dynamic source models significantly affects inter-frequency ground motion correlations for frequencies around 0.5 Hz, whereas the effect is not apparent at lower and higher frequencies.…”
Section: Validation Examples and Research Needsmentioning
confidence: 99%